Disclosure, Concealment, and the Issue of Privacy among Selected Facebook Users (American Journal of Arts and Human Science, 2023)
More than ever, our media landscape has significantly changed, bringing about significant changes, as well, in our communication patterns and practices. Undeniably, individuals from different age ranges have incorporated social media into their day-to-day activities, and the others, into their lives. These significant changes, however, have brought forth crucial issues along privacy and usage, considering social media’s scalability, replicability, persistence, and searchability. Hence, this study entitled “Disclosure, Concealment, and the Issue of Privacy among Selected Facebook Users” attempted to answer the following research questions: (1) Is disclosure a practice among the respondents? If so, what do they disclose about themselves? (2) How do they disclose? Do they disclose freely or selectively? (3)What do they conceal? ; (4) Why do they practice concealment?; (5) Is privacy a concern among the respondents? If so, what are their privacy practices? In an attempt to answer the aforementioned questions, the author utilized a qualitative interview questionnaire. However, due to time constraints, the interviews were conducted online. The respondents were selected using purposive sampling. Specifically, those who were observed to be active on Facebook were chosen. There were six (6) female respondents and one (1) male respondent, six (6) of whom are working, though not all of them indicated their specific jobs. It was found that disclosure is, indeed, a practice. However, the respondents disclosed rather selectively. Thus, there were certain information that they did not disclose/chose to conceal. Privacy was also found to be a concern among the respondents and this is reflected in their privacy practices.